Influence of organic nutrient sources and moisture management on productivity, biofortification and soil health in pearl millet (Pennisetum glaucum) + clusterbean (Cyamopsis tetragonaloba) intercropping system of semi-arid India - BANA, R S; POONIYA, V; CHOUDHARY, ANIL K; RANA, K S; TYAGI, V K (The Indian Journal of Agricultural Sciences, 2016)
A field experimentation was carried out at New Delhi, India for three years (2010-12) under rainfed semi-arid conditions to assess the effect of three organic nutrient sources and two moisture management practices on productivity, biofortification and soil health under pearl millet [Pennisetum glaucum (L.) R. Br. emend Stuntz] + clusterbean [Cyamopsis tetragonaloba (L.) Taub] intercropping system (PCIS). In current study, the pearl millet grain yield under sole pearl millet was at par with PCIS while its stover yield reduced by 5%. Under PCIS, inclusion of clusterbean led to significant reduction in clusterbean yield compared to its sole stand, however, PCIS system productivity was more over their sole crop stands, indicating that additive series of PCIS may bring more net economic gains over their sole stands in semi-arid ecology of India. The coarse cereal-legume interactions under PCIS have also led to improved protein content in pearl millet (11.2%) over its sole stand (10.7%). Zinc (Zn) and iron (Fe) deficiency is a common feature in semi-arid India and the crops grown as well. Study revealed that Zn and Fe content in pearl millet were increased by 6.5 and 1.6%, respectively, by the inclusion of clusterbean in PCIS. Plant growth, yield attributes and yield of pearl millet and clusterbean crops showed an improvement under flat sowing + organic mulching (FS+OM) over ridge and furrow sowing (RFS) but the differences were non-significant. Among organic nutrient sources, leaf compost (LC) @ 10 t/ha and FYM @ 10 t/ha produced significantly more system productivity in terms of pearl millet-equivalent-yield (PEY) than 100% RDF and control. Protein content both in pearl millet and clusterbean, and Zn and Fe biofortification in pearl millet grains was higher under FYM treated plots closely followed by LC, and leaf + cowdung mixture compost. Application of organics especially FYM @ 10 t/ha also resulted in improved soil health in terms of bulk density, soil organic carbon and NPK status after three years experimentation.